Sagot :
Answer:
Step-by-step explanation:
f (x) = 3x^2 - 4x + 1
1. f (1) = 3 (1)^2 - 4 (1) + 1
f (1) = 3 (1) - 4 (1) + 1
f (1) = 3 - 4 + 1
f (1) = 0
2. f (0) = 3 (0)^2 - 4 (0) + 1
f (0) = 3 (0) - 4 (0) + 1
f (0) = 1
3. f (-1) = 3 (-1)^2 - 4 (-1) + 1
f (-1) = 3 (1) - 4 (-1) + 1
f (-1) = 3 + 4 + 1
f (-1) = 8
4. f (3x) = 3 (3x)^2 - 4 (3x) + 1
f (3x) = 3 (9x^2) - 4 (3x) + 1
f (3x) =27x^2 - 12x + 1
5. f (x + 1) = 3 (x + 1)^2 - 4 (x + 1) + 1
f (x + 1) = 3 (x ^2 + 2x + 1) - 4 (x + 1) + 1
f (x + 1) = 3x^2 + 6x + 3 - 4x - 4 + 1
f (x + 1) = 3x^2 + 2x
sana tama